METHODOLOGICAL ASPECTS OF ASSESSING THE LEVEL OF YOUNGER STUDENTS’ SPEECH DEVELOPMENT ON THE BASIS OF AN INTEGRAL INDICATOR FOR THE PURPOSES OF SPEECH DIAGNOSTICS - Alexandrovna Shulekina, Julia; Georgievna Prikhodko, Oksana; Vladimirovna Dmitrieva, Olga (Revista Inclusiones, 2019)
The article touches upon the topical question for the speech therapy practice of accuracy and informativeness for the specialists in the methods of psychological and pedagogical examination of speech of younger school children. The hypothesis of this studywas the assertion that when developing new diagnostic methods, one should pay more attention to the combination of separate speech or language tests in the structure of the whole method, as well as assess their influence on the overall result to obtain the accurate data about the level of speech development of students and the nature of the identified violations. The most important criterion of a diagnostic technique should be the accuracy of the result. To diagnose the level of the speech development of younger school children, it is proposed to apply an integral indicator of the speech development, developed with the use of an integral score method